Remote measurement of urinary radioactivity in 18F-FDG PET patients using Compton camera for accuracy evaluation of standardized uptake value. (25th October 2018) - Watanabe, Takara; Kano, Daisuke; Enomoto, Ryoji; Muraishi, Hiroshi; Wakamatsu, Ryo; Katagiri, Hideaki; Kagaya, Mika; Kondo, Ryotaro; Fukushi, Masahiro; Hosokawa, Syota; Takeda, Tohoru; Tanaka, Manobu M; et al.
Abstract: Currently, the most commonly used estimate of metabolic activity during clinical positron emission tomography (PET) is standardized uptake value (SUV) obtained from 18 F-fluorodeoxyglucose ( 18 F-FDG) captured in cancer cells. Although SUV is evaluated after corrections for the injected dose, weight, and other such parameters, the entire injected dose is inappropriate for this calculation because some FDG is excreted in urine. Therefore, the injected dose warrants correction by assessment of urinary radioactivity in patients before PET to enhance the accuracy of FDG calculation. However, this is not typically performed in clinical practice owing to secondary effects of radioactive contamination in hospitals and radiation exposure risk to the attending staff. Therefore, we aimed to develop a remote method for the measurement of urinary radioactivity in FDG-PET patients. Urinary radioactivity was estimated in a toilet bowl using gamma-ray distribution obtained with a Compton camera. The gamma-ray events from the toilet bowl per unit time (5 s) facilitated radioactivity calculation. Between 0 and 40 MBq, deviation of our detector from the linearity for radioactivity was <8.3%. The accuracy of radioactive assessment was ±11% for a 5-s measurement of 19.7 MBq 18 F-FDG. Overall, we obtained 75 samples (45 males and 30 females). Our results revealed that excretion of FDG in the urine per person varied between 1.9% and 15.6% of the injected dose (range, 225–305 MBq). Urinary radioactivity can be evaluated before PET using a Compton camera. SUV determination in clinical context could be enhanced by considering urinary radioactivity for corrections caused by individual differences in radioactivity.